An elastic-plastic stress analysis in a unidirectional reinforced steel fiber thermoplastic composite cantilever beam loaded by a single force at the free end - Arslan, N; Özben, T (Sage Publications Ltd, 2005)
In this study an elastic-plastic analysis is carried out in a unidirectional reinforced thermoplastic composite cantilever beam loaded by a constant single force at its free end. The composite beam consists of stainless steel fiber and low-density homogeneous polyethylene matrix. An analytical solution is performed for satisfying both the governing differential equation in the plane stresses case and boundary conditions for small plastic deformation. The composite material is assumed to be hardening linearly. The Tsai-Hill theory is used as a yield criterion. The intensity of the residual stress components of sigma(x) is at the maximum at the upper or lower surfaces of the beam.
Keywords: elastic-plastic stress analysis; thermoplastic composite beam; residual stress